Reduced egfr, elevated urine protein and low level of personal protective equipment compliance among artisanal small scale gold miners at Bibiani-Ghana: a cross-sectional study - Afrifa, Justice (BMC Public Health, 2017)
BACKGROUND: Mercury is a toxic metal with its effects on human health ranging from acute to chronic in a very short time of exposure. Artisanal and small-scale gold mining (ASGM) is the main source of direct human exposure to mercury. AIM: To access the effect of mercury exposure on the renal function and level of personal protective equipment (PPE) compliance among small-scale gold miners in Bibiani District of the Western Region of Ghana METHOD: 110 consenting male gold miners were purposively recruited for this study. A structured questionnaire was used to collect socio-demographic information from the participants. Work place assessment and interviews were conducted. Urine samples were analysed for protein; blood was analysed for mercury and creatinine. Estimated glomerular filtration rate (eGFR) was calculated using the chronic kidney disease-epidemiology collaboration (CKD-EPI) equation. RESULTS: Of the 110 participants, 61(55.5%) exceeded the occupational exposure threshold (blood mercury <5μg/L). Urine protein (41.72±68.34, P<0.0001), serum creatinine (2.24±1.19, P<0.0001) and blood mercury (18.37±10.47, P<0.0001) were significantly elevated among the exposed group compared to the non-exposed group. However, the exposed group had a significantly reduced eGFR (P<0.0001). There was a significant correlation (r=0.7338, p<0.0001) between blood mercury concentration and urine protein concentration. An increase in blood mercury correlated negatively (r = −0.8233, P<0.0001) with eGFR among the exposed group. High urine protein (P< 0.0001) and high serum creatinine (P< 0.0001) were significantly associated with increased mercury exposure. Increased mercury exposure was significantly associated with burning of amalgam (P=0.0196), sucking of excess mercury (P=0.0336), longer work duration (P=0.0314) and low educational background (P=0.0473). CONCLUSION: Small scale miners at the Bibiani work site are exposed to excess mercury. Proteinuria and reduced eGFR is common in mine workers exposed to excess mercury. We found poor PPE compliance among the study population.